Second-order sliding mode optimization control of an inverted pendulum system based on fuzzy adaptive technology - Leng, Xuefeng (Frontiers in Mechanical Engineering, 2024)
IntroductionThis paper aims at the control problem of nonlinear systems with uncertainty in general, and avoids the deviation of sliding mode controller from the preset constraint region during the convergence process.MethodsA sliding mode control method based on fuzzy adaptive technique was proposed by constructing obstacle Lyapunov function (BLF). Design problem of fuzzy adaptive second-order sliding mode controller considering output constraints. The Lyapunov function of the cutting barrier is designed, and the fuzzy adaptive second-order sliding mode controller is constructed by combining the Lyapunov function with the regression method. A second-order finite output sliding mode controller is designed for the inverted pendulum system. In the case of unknown external disturbance, the mathematical modeling and force analysis of the first order inverted pendulum system are carried out, and the design problem of the fuzzy adaptive second-order sliding mode controller with output restriction is studied.Results and DiscussionThe proposed fuzzy adaptive second-order sliding mode controller has a good control effect in the inverted pendulum system. The fuzzy adaptive second-order controller stabilizes the sliding mode at 0.1 in 1.25 s, while the fuzzy adaptive second-order controller makes the system state reach equilibrium in 15 s. The accuracy of fuzzy adaptive second-order sliding mode controller reaches 99.2%, which is superior to other methods in terms of balance accuracy and recall rate. The controller not only has a fast response speed, but also can effectively suppress system flutter and ensure the rapid stability of the system after constraints. This research method lays a foundation for the design of fuzzy adaptive sliding mode control algorithm.